IMPLEMENTATION OF THE ENDEMIC ANIMAL PROTECTION POLICY FOR KAKATUA JAMBUL KUNING BIRD ON MASAKAMBING ISLAND MASALEMBU DISTRICT SUMENEP - Andika, Dwi; Mardika, Suluh (JURNAL SETIA PANCASILA, 2025)
This study aims to evaluate the implementation of protection policies for the bird kakatua jambul kuning in the area, as well as to identify factors that influence the success of endemic animal protection.Data collection was carried out using interview, observation and documentation techniques. After the data is collected, the analysis is carried out through several stages, namely data reduction, data presentation, and drawing conclusions. The object of the research is the implementation of policies related to endemic animals, especially the yellow-crested parrot, on Masakambing Island.The research results show that the conservation policy instrument for the protection of animal regulations contained in Presidential Decree of 1978, Law of 1990, and Government Regulation of 1999, East Java Governor's decision 188/166/KPTS/013/2020 and Masakambing Village regulation number 1/perdes/435.424.103/2009, these regulations are regulations that sheltering the Kakatua Jambul Kuning bird. Implementation of the conservation of the endemic Kakatua Jambul Kuning bird on Masakambing Island within a bureaucratic structure often results in miscommunication between superiors and field workers, as well as coordination between office workers and guards in the field is hampered because the facilities and infrastructure are not met.